Analyzing and identifying novel B cell epitopes within Toxoplasma gondii GRA4 - Wang, Yanhua; Wang, Guangxiang; Ou, Jiangtao; Yin, Hong; Zhang, Delin (Parasites & vectors, 2014)
BACKGROUND: The identification of specific epitopes targeted by the host antibody response is important for understanding the natural response to infection and for the development of epitope-based marker vaccines and diagnostic tools for toxoplasmosis. In this study, Toxoplasma gondii GRA4 epitopes were identified using software-based prediction and a synthetic peptide technique. METHODS: The complete GRA4 gene sequence was obtained from T. gondii of the Gansu Jingtai strain of tachyzoites. The potential B cell epitopes of GRA4 was predicted using the PROTEAN subroutine in the DNASTAR software package. The peptides with good hydrophilicity, high accessibility, high flexibility and strong antigenicity were chemically synthesized and assessed by ELISA using pig sera from different time points after infection. RESULTS: The potential B cell epitopes of GRA4 predicted by bioinformatics tools focused on six regions of GRA4, 52–77 aa, 93–112 aa, 127–157 aa, 178–201 aa, 223–252 aa and 314–333 aa. Eleven shorter peptides from the six regions were synthesized and assessed by ELISA using pig sera from different time points after infection. Three of the eleven peptides (amino acids 62–77, 233–252 and 314–333) tested were recognized by all sera. CONCLUSIONS: We precisely located the T. gondii GRA4 epitopes using pig sera collected at different time points after infection. The identified epitopes may be useful for additional studies of epitope-based vaccines and diagnostic reagents.